2016
DOI: 10.5762/kais.2016.17.8.172
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Nursing Students' Learning Experience, Recognition of Importance and Learning Self-efficacy for Core Fundamental Nursing Skills on their Self-confidence

Abstract: This study is a descriptive survey research conducted to examine the influence of learning efficacy on nursing students' self-confidence. Research subjects included a total of 231 university students in D city, and the data were analyzed by t-test, ANOVA, Pearson's correlation coefficients, and multiple regression. The study results were as follows: Learning experience was high in the order of vital sign check, intramuscular injection, and subcutaneous injection. Recognition of importance was also high in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
4
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 13 publications
3
4
0
1
Order By: Relevance
“…Moreover, professor-student interaction was an influencing factor of self-esteem. This agrees with Lee et al [13], who reported that interpersonal relationships influence nurses' well-being, satisfaction, and self-esteem, and with Kim and Kang [39], who showed that better interpersonal relationships are associated with a higher self-esteem. Although clinical instructors' roles (i.e., provide guidance at the practicum site) is important, the results of the current study underscore the importance of the professors' roles during the clinical practicum period and in online settings by showing that only professor-student interactions were influencing factors of self-esteem.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Moreover, professor-student interaction was an influencing factor of self-esteem. This agrees with Lee et al [13], who reported that interpersonal relationships influence nurses' well-being, satisfaction, and self-esteem, and with Kim and Kang [39], who showed that better interpersonal relationships are associated with a higher self-esteem. Although clinical instructors' roles (i.e., provide guidance at the practicum site) is important, the results of the current study underscore the importance of the professors' roles during the clinical practicum period and in online settings by showing that only professor-student interactions were influencing factors of self-esteem.…”
Section: Discussionsupporting
confidence: 91%
“…Further, Alshahrani et al [38] showed that nursing college students may experience difficulties during a clinical practicum as they feel the limits of their abilities because of their lack of skills [38]. Confidence has also been shown to be related to self-efficacy and major satisfaction [39,40]. Together, these results indicate the need for educational methods that improve nursing college students' confidence in their core nursing skills.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, the rate of participants who reported an increase in neonatal nursing confidence was 89%, regardless of the change in their self-efficacy after completing the neonatal nursing practice program, which indicates that students' confidence generally increased. Although a direct comparison cannot be made due to the lack of previous studies in which nursing practice-related confidence and self-efficacy were analyzed, these results correspond to those of previous studies [26,27], in which higher self-efficacy increased confidence in practice. This study used hands-on practice with dummy infants to help students perform successfully on specific assignments and activities, while also providing them with skills necessary for social situations.…”
Section: Chnrsupporting
confidence: 82%
“…, 전공만족도 [5][6][7], 자기효능감 [8,9], 학습 전이 [10], 연령 [11] 등 다양한 요인에 의해 영향을 받는 것으로 보고되고 있다. 대체로 전공적합도 혹은 전공만족도가 높을수록 임상수행자신감이 높은 것으로 보이며 [5,7], 또한 자기효능감이 높은 학생은 핵심기본간호술 수행 시에 과업 수행 신념과 성공적 수행을 위한 적극적인 태도로 인해 수행자신감이 높아지고 [12], 자기효능감이 높을수록 임상수행능력이 높아지는 것으로 보인다 [11,13]…”
unclassified